2016
DOI: 10.1021/acs.nanolett.6b01994
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Activatable Versatile Micelleplexes for PD-L1 Blockade-Enhanced Cancer Photodynamic Immunotherapy

Abstract: Photodynamic therapy (PDT) has emerged as a promising clinical modality for cancer therapy due to its ability to initiate an antitumor immune response. However, PDT-mediated cancer immunotherapy is severely impaired by tumor-cell immunosuppression of host T cell antitumor activity through the programmed cell death 1 ligand (PD-L1) and programmed cell death receptor 1 (PD-1) (PD-L1-PD-1) immune checkpoint pathway. Here, we demonstrate that PDT-mediated cancer immunotherapy can be augmented by PD-L1 knockdown (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
283
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 380 publications
(292 citation statements)
references
References 45 publications
8
283
0
1
Order By: Relevance
“…Much more is however expected from the nanotechnology side for the possibility of exploiting passive and active mechanisms of targeting the tumors and combining more drugs in well engineered nanoplatforms for the combination of PDT with other treatment modalities. In this context, particular attention should be given to combinations including immunotherapeutics able to potentiate the immunological response elicited by PDT producing systemic antitumor effects impacting also in metastasis located far from the primary tumor treated with PDT [161,163].…”
Section: Discussionmentioning
confidence: 99%
“…Much more is however expected from the nanotechnology side for the possibility of exploiting passive and active mechanisms of targeting the tumors and combining more drugs in well engineered nanoplatforms for the combination of PDT with other treatment modalities. In this context, particular attention should be given to combinations including immunotherapeutics able to potentiate the immunological response elicited by PDT producing systemic antitumor effects impacting also in metastasis located far from the primary tumor treated with PDT [161,163].…”
Section: Discussionmentioning
confidence: 99%
“…[263] Platforms designed for combinations of cancer immunotherapy and nonsurgical treatment were reviewed in detail by Nam and colleagues. [271][272][273][274][275][276][277][278] A recent study reported that the combination of PDT and autophagy inhibitor after resection of orthotopic xenograft osteosarcoma observed an enhanced antitumor effect by suppressing PD-L1 expression, which indicated the potential surgical application of photodynamic-immunotherapy to improve outcomes and longterm survivals. [264][265][266][267][268][269][270] The cascaded synergistic effects of photodynamic-immunotherapy can provide a promising strategy to inhibit both primary lesions and distant metastases, which can be hardly achieved by conventional PDT with limited immunologic effects.…”
Section: Postoperative Immunotherapy For Long-term Antitumor Effectsmentioning
confidence: 99%
“…In order to elevate the intratumoral level of IL-12, Gou and co-workers designed a biodegradable nanoparticle composed of heparin-polyethyleneimine conjugate for tumor-targeted delivery of two plasmids encoding vesicular stomatitis virus matrix protein (VSVMP) and IL-12 ( Figure 3A). [121] Copyright 2016, American Chemical Society. In this case, the nanoparticle was dosed 3 d after intraperitoneal injection of CT-26 cancer cells, when immunosuppressive TME had not been fully established to inhibit the activity of recruited CTLs and NK cells.…”
Section: Nanomedicine For Cytokine Modulationmentioning
confidence: 99%